Epiphytic diatom composition on the leaf blades of Enhalus acoroides in Almeria Biliran, Philippines during the cold dry season of 2012-2013 - Baqueros, April Rose S.; Yap-Dejeto, Leni (2013)
Epiphytic algae are important component of seagrass ecosystem. They can act as indicators of biodiversity and ecological status. This study primarily aimed to assess the epiphytic diatom in the leaves of seagrass species, Enhalus acoroides in Almeria coastal region within a three-month sampling period. Epiphytes were scraped-off from the leaf surfaces of the seagrass and identified under a compound light microscope. A total of 10 species of epiphytic diatoms were observed. These were Bacillaria sp., Cyclotephanos sp., Navicula sp.1, Navicula sp.2, Thalassiothrix sp., Cocconeis sp., Thalasiosira sp., Pleurosigma sp., Chaetoceros sp. and Rhizosolenia sp. Family Naviculaceae dominated all the sampling stations that constituted 46% of the total diatoms. Variation of species abundance and richness between sites was observed. In all stations, Navicula were the highest cell density. It was also the prevailing species in different stations. While the secondary and accompanying species varied in each stations. Stations 1 and 3 are more diverse compared to station 2. The site more disturbed by human activities had a significantly smaller abundance and species richness.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Algae